In vitro Activity of Robenidine Analog NCL195 in Combination With Outer Membrane Permeabilizers Against Gram-Negative Bacterial Pathogens and Impact on Systemic Gram-Positive Bacterial Infection in Mice - Pi, Hongfei; Nguyen, Hang Thi; Venter, Henrietta; Boileau, Alexandra R.; Woolford, Lucy; Garg, Sanjay; Page, Stephen W.; Russell, Cecilia C.; Baker, Jennifer R.; McCluskey, Adam; O’Donovan, Lisa A.; Trott, Darren J.; et al. (Frontiers in Microbiology, 2020)
Multidrug-resistant (MDR) pathogens, particularly the ESKAPE group (Enterococcus faecalis/faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Escherichia coli and Enterobacter spp.), have become a public health threat worldwide. Development of new antimicrobial classes and the use of drugs in combination are potential strategies to treat MDR ESKAPE pathogen infections and promote optimal antimicrobial stewardship. Here, the in vitro antimicrobial activity of robenidine analog NCL195 alone or in combination with different concentrations of three outer membrane permeabilizers (ethylenediaminetetraacetic acid (EDTA), polymyxin B nonapeptide (PMBN) and polymyxin B (PMB)) was further evaluated against clinical isolates and reference strains of key Gram-negative bacteria. NCL195 alone was bactericidal against Neisseria meningitidis and N. gonorrhoeae (MIC/MBC = 32 µg/ml) and demonstrated synergistic activity against P. aeruginosa, E. coli, K. pneumoniae and Enterobacter spp. strains in the presence of sub-inhibitory concentrations of EDTA, PMBN, or PMB. The additive and/or synergisitc effects of NCL195 in combination with EDTA, PMBN or PMB are promising developments for a new chemical class scaffold to treat Gram-negative infections. Tokuyasu cryo ultramicrotomy was used to visualize the effect of NCL195 on bioluminescent S. aureus membrane morphology. Additionally, NCL195’s favorable pharmacokinetic (PK) and pharmacodynamic (PD) profile was further explored in in vivo safety studies in mice and preliminary efficacy studies against Gram-positive bacteria. Mice administered two doses of NCL195 (50 mg/kg) by the intraperitoneal (IP) route 4 hours apart showed no adverse clinical effects and no observable histological effects in major organs. In bioluminescent S. pneumoniae and S. aureus murine sepsis challenge models, mice that received two 50 mg/kg doses of NCL195 4 or 6 hours apart exhibited significantly reduced bacterial loads and longer survival times than untreated mice. However, further medicinal chemistry and pharmaceutical development to improve potency, solubility and selectivity is required before efficacy testing in Gram-negative infection models.